Establishment and application of China's first pediatric rational medication intelligent decision system database - Wu, Dan; Zheng, Feng; Chen, Yang; Zhang, Xuhui; Xu, Yin; Chen, Hao; Zhou, Yuxuan; Ni, Wenjie; Zhang, Xiaobo; Wang, Yi; Li, Zhiping (Frontiers in Pediatrics, 2026)
ObjectiveThe incidence of medication errors is much higher among children because of their unique characteristics. This study aims to establish the first Pediatric Rational Medication Intelligent Decision System (PRMIDS) database in China and apply it to the preprescription review system to enhance the safety and effectiveness of medication therapy in children.MethodsThe PRMIDS database was built on authoritative drug information reference books and websites. All drug information was collected, screened, and verified by at least two senior pharmacists. After ensuring consistency with actual local drug use, the information was entered into the system. Based on the severity of potential outcomes, the warning levels of drug information in the PRMIDS were classified into three categories: red (Level 7, absolutely prohibited), yellow (Level 6, relatively prohibited), and green (Levels 1–5, use with caution).ResultsBetween November 2018 and June 2025, over 400,000 data entries for 1,030 drugs were integrated. Drug information included conventional dosage, maximum dosage, administration routes, frequency, duplication, drug–drug/drug–food interactions, solvents and compatibility of injections, concentration and administration duration of infusion, allergies, pharmacogenomics, compatibility of Chinese Patent Medicines and Traditional Chinese Medicine, and requirements for decoction. After the PRMIDS database was embedded into the hospital information system, it could automatically obtain the real-time disease status and the latest examination results of children. The implementation of the PRMIDS led to a significant, non-linear reduction in Level 6 prescription alerts. A regression analysis showed a significant decline in Level 6 prescriptions after implementation (p < 0.001).ConclusionThe PRMIDS is the first medication information system specifically designed for Chinese children. This study proves its clinical impact and suggests potential for scalability and generalizability across China.